THE NEUROPROTECTIVE EFFECT OF HONEY’S POLYPHENOL FOR THE POTENTIAL TREATMENT OF NEURODEGENERATIVE DISEASES: A SYSTEMATIC REVIEW - Soenarti, Sri; Nanda Utama, Gede; Utomo, Vidi Prasetyo (MNJ (Malang Neurology Journal), 2025)
Background: Neurodegenerative disorders, such as Alzheimer's and Parkinson's, are distinguished by the progressive deterioration of the central nervous system's structure and functionality. Their pathophysiology is significantly influenced by neuroinflammation and oxidative stress. Natural honey, high in polyphenols and flavonoids, may be useful in the treatment of various ailments. Methods: This systematic review follows the PRISMA guidelines, covering literature searches conducted from June 1 to July 20, 2024. Included studies were published in the last decade and focused on the effects of honey on neurodegenerative diseases. Results: The review included six studies, comprising four in vivo studies and two in vitro studies. The in vivo studies used rodents and nematodes as subjects. Honey demonstrated significant neuroprotective effects in Parkinson's disease models, including improved motor coordination and reduced neuronal damage. In Alzheimer's disease models, honey reduced amyloid-β aggregation and enhanced antioxidant defences. Discussion: The studies indicate that honey has anti-inflammatory and antioxidant benefits, helping to reduce oxidative stress and prevent neuronal damage. The polyphenols and flavonoids in honey also increased the concentration and activity of antioxidant enzymes such as glutathione (GSH) and superoxide dismutase (SOD). Additionally, honey can boost the expression of Brain-Derived Neurotrophic Factor (BDNF), which is crucial for synaptic plasticity and cognitive performance. Conclusion: Honey, particularly its polyphenol and flavonoid components, shows potential as a neuroprotective agent for neurodegenerative diseases. However, further research, especially clinical trials in humans, is needed to confirm these findings and explore the therapeutic potential of honey more comprehensively.